Međimurje Sustainable Development Program (University of Maribor Press, 2023)
Međimurje Sustainable Development Program. In the north of Croatia, surrounded by Mura and Drava rivers, lies the Međimurje County. Although spatially the smallest county in the Republic of Croatia, it has a rich history, cultural heritage, thoughtful and strategic tourism, and was awarded many titles. Therefore, this tourist destination of excellence can serve as an example of good practice for the students of the field course, which was attended by sixty students and eight faculties from the Republic of Croatia, Slovenia, but also numerous Erasmus students from Spain, Norway, the Netherlands and Montenegro, who during their two-day visit were able to see the great development potential of this county. Accompanied by their mentors and under the professional guidance of their hosts, the students analyzed the current tourism offer and development challenges in each location visited and, as part of their work, identified the priority areas of tourism, defined measures and indicators, and how to monitor them. All the work is based on the sustainable development of tourism. Scientific Monograph " Međimurje Sustainable Development Program" is the result of initiatives of local stakeholders to promote the strategic development of tourism in Central Croatia and Međimurje County.